(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This abstract presents the idea of ​​artificial intelligence at the service of the Citizen Justice, as well as its importance for society, thus improving the quality of life of the human being. It discusses the controversial issue involving favorable and contrary opinions on the subject, using technical bibliographical and documentary procedures, classifying the research as qualitative regarding the approach of the problem and exploratory as to the general object, so as to use the dialectical method. Finally, the study comprehends the need for information and organization on the part of the State and society, seeking a reeducation regarding the care with the environmental space in which the man is inserted, including the technological evolutions.